Elemental analysis of unprocessed cola nitida seed using EDX-VPSEM. - Othman, Fauziah; Rahmat, Asmah; W.M.Z, Wan Noor Izzah; Suherman, J.; Susi, E.; Goriman Khan, Mohd Azam Khan; Kadivar, Mohammad (Universiti Putra Malaysia, 2008)
For a long time, mineral, plant and animal products were the main source of drugs. Potassium is important in regulating the transfer of nutrients to the cells, phosphorus plays a role in metabolic reaction in the body, while magnesium plays a significant role in photosynthesis, carbohydrate metabolism, nucleic acids and binding agents of cell walls. The objective of this study was to analyze the mineral content of Cola nitida seed with EDX-VPSEM. Unprocessed (fresh) Cola nitida seeds were observed for their surface morphological structure under SEM. Together with the image, elemental analysis using EDX was carried out by using SEM. Scanning electron micrograph of Cola nitida seed illustrated numerous crystals can be seen distributed in clusters within the cell wall. The crystals were variable in shape and size with diameter ranging from 2 to 10 μm. The crystals were densely packed with limited space in between them. The elemental analysis results showed that the sample consisted of many important minerals like oxygen (49.79 ± 0.36 %), carbon (47.56 ± 0.33 %), potassium (1.93 ± 0.15 %), phosphorus (0.43 ± 0.08 %) and magnesium (0.27 ± 0.05 %). In conclusion, Cola nitida seed was shown to have useful minerals and further investigation will be carried out to study more beneficial medicinal properties of this plant.